Saving Rates in Latin America: A Neoclassical Perspective (2019)
This paper examines the time path of saving rates between 1970 and 2010 in Chile, Colombia, and Mexico through the lens of the neoclassical growth model. The findings indicate that two factors, the growth rate of TFP and fiscal policy, are able to account for some of the major fluctuations in saving rates observed during this period. In particular, we find that the model accounts for the low saving rates in Chile compared to Colombia until the late 1980s and the reversal in the saving rates thereafter. Also, a combination of high TFP growth and tax reforms that substantially reduced capital taxation seems to be responsible for the impressive increase in Chile’s saving rate in mid 1980s.